Defined integrals in the determining of characteristics in metallic structures in the construction of a warehouse - Moreira, Juracy Mendes; Oliveira, Wender Marcos; Goncalves, Douglas Gomes; Nascimento, Paulo Henrique do; Silva Junior, Elielton Olimpio da; Brito, Gisley de Souza (Pubvet, 2024)
The objective proposed in this study will be to present a practical application of the use of the content of defined integrals in determining certain geometric characteristics in fundamental metallic structures in civil construction, knowing that there is a concern on the part of teachers and pedagogical coordinators regarding the teaching and learning of specific subjects, leading students to a lack of stimulation and, consequently, the much-feared dropout. As an application of the use of integrals, we can consider a civil engineer who has planned the construction of an agricultural shed and knows that the roof of the structure is described by a quadratic function of the type . Even though this structure is subject to a transverse shape resulting from its own weight and the weight of other structures that are supported on it. In cases where geometry proves to be inefficient, we will introduce the concept of the definite integral. Let
Keywords: Architecture; centroid; gravity